Environmental Transport and Transformation of Pollutants (MDPI - Multidisciplinary Digital Publishing Institute, 2026)
The presence of various pollutants in the environment causes concern due to their potential adverse effects on the ecosystem and human beings. Pollutants such as heavy metals, chlorinated solvents, petroleum hydrocarbons, polycyclic aromatic hydrocarbons, polychlorinated biphenyls, polybrominated diphenyl ethers, per- and poly-fluorinated compounds, pesticides, antibiotics, micro- and nano-plastics, etc., may be transported and transformed in the environment, and these processes are influenced by many factors, such as the physical, chemical, and biological properties of the pollutants, the physio-chemical and biological properties of the matrix, and environmental conditions. Understanding the environmental processes of pollutants as well as their effects helps to establish sound science-based regulations and develop effective management practices. This Special Issue offers insights into advanced research in the environmental processes of pollutants. Potential topics include, but are not limited to, the following: (1) Technologies for measurements of pollutants; (2) Approaches to characterize environmental transport and transformation; (3) Methods to predict and quantify environmental processes; (4) Assessments of interactions between pollutants and the environmental matrix; (5) Effects of transport and transformation of pollutants.